Transcriptional Inhibition of AGPAT2 Induces Abnormal Lipid Metabolism and Oxidative Stress in the Liver of Nile Tilapia Oreochromis niloticus - Tiantian Feng; Yifan Tao; Yue Yan; Siqi Lu; Yan Li; Xing Zhang; Jun Qiang (MDPI AG, 2023)
The enzyme 1-acylglycerol-3-phosphate O-acyltransferase 2 (AGPAT2) is an intermediate enzyme in triglyceride synthesis. The aim was to study the regulatory mechanism of AGPAT2 on Nile tilapia, Oreochromis niloticus. In this study, antisense RNA technology was used to knock-down AGPAT2 in Nile tilapia. Compared with the control groups (transfected with ultrapure water or the blank expression vector), the AGPAT2 knock-down group showed a significantly higher weight gain rate, special growth rate, visceral somatic index, and hepatopancreas somatic index; and significantly increased the total cholesterol, triglycerides, glucose, low-density lipoprotein cholesterol, and insulin levels in serum. In addition, the contents of total cholesterol and triglycerides and the abundance of superoxide dismutase, catalase, and glutathione peroxidase in the liver significantly increased, while the malondialdehyde content significantly decreased. The liver cells became severely vacuolated and accumulated lipids in the AGPAT2 knock-down group. Comparative transcriptome analyses (AGPAT2 knock-down vs. control group) revealed 1789 differentially expressed genes (DEGs), including 472 upregulated genes and 1313 downregulated genes in the AGPAT2 knock-down group. Functional analysis showed that the main pathway of differentially expressed genes enrichment was lipid metabolism and oxidative stress, such as steroid biosynthesis, unsaturated fatty acid biosynthesis, the PPAR signaling pathway, and the P53 pathway. We used qRT-PCR to verify the mRNA expression changes of 13 downstream differential genes in related signaling pathways. These findings demonstrate that knock-down of AGPAT2 in tilapia leads to abnormal lipid metabolism and oxidative stress.